The Impact of Variation in Foliar Constituents of Sunflower on Development and Reproduction of Diacrisia casignetum Kollar (Lepidoptera: Arctiidae) - Nayan Roy; Anandamay Barik (Psyche: A Journal of Entomology)
Effects of feeding on young, mature, and senescent sunflower leaves were studied under laboratory conditions (27 ± 0.5°C, 12L : 12D, 65±5% RH) to evaluate the impact of variation of nutrients on larval food utilization efficiency, larval and pupal development and survival, longevity, and fecundity of Diacrisia casignetum Kollar. The growth rate, which is the ratio between the dry weight gain of insect and duration of experimental period, of D. casignetum was in the order of mature leaf > young leaf > senescent leaf of sunflower. This was correlated with nutrient constituents of three kinds of sunflower leaves, which was measured by various biochemical analyses described elsewhere in the text. Total carbohydrates, proteins, lipids, nitrogen, amino acids, and water content are in greater amount in mature leaves when compared to young and senescent leaves, whereas phenol content was highest in young leaves than mature leaves. Hence, higher amount of total carbohydrates, proteins, lipids, nitrogen, amino acids including water and lower amount of total phenol content in mature leaves have influenced higher growth rate, less developmental time, and higher fecundity of D. casignetum.